Get the answers you need at Westonci.ca, where our expert community is dedicated to providing you with accurate information. Discover comprehensive answers to your questions from knowledgeable professionals on our user-friendly platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.

Question 2 of 5

State the possible rational zeros for each function. Then find all rational zeros.

[tex]f(x) = 2x^3 + x^2 - 2x - 1[/tex]


Sagot :

To determine the possible rational zeros of the polynomial [tex]\( f(x) = 2x^3 + x^2 - 2x - 1 \)[/tex] and then find all actual rational zeros, we will use the Rational Root Theorem and synthetic division. The Rational Root Theorem states that any possible rational root, [tex]\( \frac{p}{q} \)[/tex], of a polynomial is a factor of the constant term (constant term = [tex]\(-1\)[/tex]) divided by a factor of the leading coefficient (leading coefficient = [tex]\(2\)[/tex]).

### Step 1: Identify factors of the constant term and the leading coefficient
- Factors of [tex]\(-1\)[/tex]: [tex]\(\pm 1\)[/tex]
- Factors of [tex]\(2\)[/tex]: [tex]\(\pm 1, \pm 2\)[/tex]

### Step 2: List all possible rational zeros
The possible rational zeros are the fractions formed by dividing each factor of the constant term by each factor of the leading coefficient:

[tex]\[ \text{Possible rational zeros} = \left\{ \pm 1, \pm \frac{1}{2} \right\} \][/tex]

### Step 3: Test each possible rational zero
We will substitute each possible rational zero into the polynomial [tex]\( f(x) \)[/tex] to see if it equals zero.

1. Test [tex]\( x = 1 \)[/tex]
[tex]\[ f(1) = 2(1)^3 + (1)^2 - 2(1) - 1 = 2 + 1 - 2 - 1 = 0 \][/tex]
So, [tex]\( x = 1 \)[/tex] is a rational zero.

2. Test [tex]\( x = -1 \)[/tex]
[tex]\[ f(-1) = 2(-1)^3 + (-1)^2 - 2(-1) - 1 = -2 + 1 + 2 - 1 = 0 \][/tex]
So, [tex]\( x = -1 \)[/tex] is a rational zero.

3. Test [tex]\( x = \frac{1}{2} \)[/tex]
[tex]\[ f\left(\frac{1}{2}\right) = 2\left(\frac{1}{2}\right)^3 + \left(\frac{1}{2}\right)^2 - 2\left(\frac{1}{2}\right) - 1 = 2\left(\frac{1}{8}\right) + \left(\frac{1}{4}\right) - 1 - 1 \][/tex]
[tex]\[ = \frac{2}{8} + \frac{2}{8} - 1 - 1 = \frac{1}{4} + \frac{1}{4} - 1 - 1 = \frac{1}{2} - 2 = -\frac{3}{2} \neq 0 \][/tex]
So, [tex]\( x = \frac{1}{2} \)[/tex] is not a rational zero.

4. Test [tex]\( x = -\frac{1}{2} \)[/tex]
[tex]\[ f\left(-\frac{1}{2}\right) = 2\left(-\frac{1}{2}\right)^3 + \left(-\frac{1}{2}\right)^2 - 2\left(-\frac{1}{2}\right) - 1 = -2\left(\frac{1}{8}\right) + \left(\frac{1}{4}\right) + 1 - 1 \][/tex]
[tex]\[ = -\frac{1}{4} + \frac{1}{4} + 1 - 1 = 0 \][/tex]
So, [tex]\( x = -\frac{1}{2} \)[/tex] is a rational zero.

### Step 4: List all rational zeros
We found the rational zeros by plugging the possible zeros into the polynomial:
[tex]\[ \text{Rational zeros} = \left\{ 1, -1, -\frac{1}{2} \right\} \][/tex]

Thus, the possible rational zeros for the polynomial [tex]\( f(x) = 2x^3 + x^2 - 2x - 1 \)[/tex] are [tex]\(\pm 1\)[/tex] and [tex]\(\pm \frac{1}{2}\)[/tex], and the actual rational zeros are [tex]\( x = 1, x = -1, \)[/tex] and [tex]\( x = -\frac{1}{2} \)[/tex].